Pengaruh Model Pembelajaran Student Facilitator And Explaining (SFAE) Terhadap Pemecahan Soal Higher Order Thinking Skill (HOTS) - Saiful Saiful; Dian Noer Asyari; Siti Lutfiatul Mukaromah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to determine the influence of the Student Facilitator and Explaining (SFaE) learning model on solving Higher Order Thingking Skills (HOTS) problems. This research is a quasi-experimental type of quantitative research. The research site is at Al-Irsyad Junior High School Banyuwangi. The research sample is class VIII-B as the experimental class and VIII-D as the control class. The data collection technique uses observation, tests and documentation. Observation is used to observe student activities during the learning process. The research design uses Pre-Test Pos-Test Control Group Design. Sample members were given a Pre-Test with the aim of finding out students' knowledge before learning. Post-Test is given with the aim of finding out students' knowledge after learning. The results showed that there was an influence of the Student Facilitator and Explaining (SFaE) learning model on solving Higher Order Thingking Skills (HOTS) problems. This can be seen from the results of sig 0.00<0.05 showing that H0 was rejected and Ha was accepted.